Handling of fruits and seeds of forest species Inga densiflora Benth. and Inga edulis Mart. Associated to coffee landscape of department Quindío (Revista de Investigaciones Universidad del Quindío, 2013)
We evaluated morphological and physiological aspects of the fruits and seeds of Inga densiflora and Inga edulis species to contribute to the knowledge on the two of the most important tree species of coffee landscapes in Quindío. Sampling was conducted on farms in 6 municipalities of the department, by collecting the fruits and seeds. Samples were processed in the laboratory of Biotechnology Studies and Research Center for Biodiversity and Biotechnology, University of Quindío (CIBUQ), which determined the percentage of viability, moisture content, germination percentage and speed. The seedlings so obtained were taken to the nursery at the University of Quindío and the percentage of mortality and survival were assessed. We also collected fruits and seeds from tree species associated with these coffee landscapes; these seeds were processed in the Herbarium of the University of Quindío and used to establish the Carpoteca. Finally, we looked at traditional uses given to the 2 species evaluated by the community through the implementation of   survey. Tests run for Inga densiflora revealed a moisture content of 64.25%, viability 80%, germination 80% germination rate index 8.87 seeds per day. In Inga edulis seed moisture content was 43.68%, the percentage of viability and germination was 100% in both cases and the germination rate index of 16.15. The mortality rate was 40% in Inga densiflora and of 58.30% in Inga edulis. The CIBUQ’s Carpoteca has a total of 73 accessions distributed in 29 families, 59 genera and 71 species. We identified that Guamo species have uses by local people: to shade coffee plantations, food and firewood. Guamo species as other tropical tree species have recalcitrant seeds, as evidenced by their seed high moisture content. Overall, the percentage of viability and germination coincided with reported data for other species of the same genus. The seedling mortality rate was high in both species compared with other reports.
Keywords: Fruits; seeds; tree species; seed storage; coffee cultural landscape